A mobile educational learning experience: From digital illiterate pre-service teachers to digital literate pre-service teachers - Rodriguez-Pichardo, Catalina (IJRDO - Journal of Social Science and Humanities Research, 2017)
Teachers have to be aligned with the new educational demands, so integrating technology in a mobile educational system and applying self-regulation competence appear to be the solution for pre-service teachers willing to become digital literate pre-service teacher that includes Information and Communication Technology (ICT) into their educational practices. The purpose was to describe what self-regulatory and technological skills use some mobile learners from the Caribbean, South, Central and Northern America for being high achiever in this educational system that enable them to apply technology into their own practice. After the ethic code was followed and a validated instrument was applied, the data was processed using descriptive and inferential analyses. Some of the factors that were found to be relevant for being high achievers and being advanced technology users were: selfefficacy (p=0.011); task persistence (p=0.049); self-esteem (p=0.013); and having computer experience (p=0.007). Some academic reflections are included too.